Notes on rare and threatened flora in western-central Iberia - Ramírez-Rodríguez, Rubén; Amich, Francisco (Lazaroa, 2014)
Here we provide new records for the Natural Park of Las Arribes del Duero (Salamanca-Zamora) regarding six rare and endangered plants in western central Iberia. We also discuss different aspects from the point of view of conservation and the current status of new populations.